Abordagem biopsicossocial no controle postural e realidade virtual não imersiva em crianças e adolescentes com Paralisia Cerebral - Arnoni, Joice Luiza Bruno (2019)
According to the Classification of Functioning, Disability and Health (ICF), the health condition of an individual is a result of the multidimensional relationship between body structure and function, activities and social participation, and contextual factors. Considering that contextual changes may influence body stability in children, such as conditions of the base of support (feet positioning) and support surface (compliance, adhesion, inclination), this study was developed to verify the effects of manipulations of the base of support and support surface in postural control in children and adolescents. It was found that the manipulation of the base of support and support surface are factors that can increase the adaptive demands of the postural control system, especially in children with neuromotor dysfunctions such as Cerebral Palsy (CP). Managing challenging daily situations for postural control is one of the objectives of the rehabilitation programs for children with CP. Thus, new therapeutic tools have been used and non-immersive Virtual Reality (VR) is one of them, able to provide contextualized training and with high repetitions. However, there were no controlled studies to verify the effects of non-immersive RV on postural control in more challenging postural conditions of children with CP. Thus, motivation for study II was found, which verified the effect of training with non-immersive RV on postural oscillation in orthostatism in different conditions of the support base and malleability of the support surface in children and adolescents with unilateral CP. It was observed a reduction of postural oscillation (medial-lateral amplitude and medial-lateral RMS) after the intervention period, in the malleable surface conditions and increase in the mean velocity in the most complex condition (malleable surface and semi-tandem feet) in the group after the training period. It is concluded that VR can improve specific parameters of body stability in children with CP. Little is known about the effects of non-immersive VR in performing dynamic activities, such as gait. Thus, study III was developed, with the objective of investigating changes in functional mobility, temporal space variables and pelvic angles after non-immersive RV intervention. The results indicated an improvement in the functional mobility, in the temporal space variables of the gait, such as reduction of the time of the last, increase of the cadence and gain of stabilization of the pelvic movements, with reduction of the angles for pelvic retroversion in the intervention group. In order to increase knowledge about the effects of VR, considering that motor damage can impact personal factors, study IV was developed, which verified the effects of VR for aspects of self-concept, general motor performance, balance and increase in adaptive success in games. It is concluded that non-immersive VR can optimize aspects of body structure / function, through changes in body stability, mobility, space-time gait and angular parameters of the pelvis, execution of activities and influence on contextual factors such as modifications in self-concept. Therefore, non-immersive VR through the use of an active video game should be considered as a complementary therapeutic tool in the rehabilitation of children with CP spastic unilateral with mild impairment.